Young Adults’ Mental Health and Commitment to Exercise during the COVID-19 Pandemic - Carley, Joshua (Université d'Ottawa | University of Ottawa, 2025)
Mental health issues, particularly anxiety and depression, continue to show an upward trend among young adults in Canada. This persistent increase has prompted researchers to investigate various treatment modalities, with physical activity emerging as a promising intervention. Evidence shows that engagement in physical activity can alleviate symptoms of anxiety and depression, with neurochemical effects comparable to pharmacological interventions, such as selective serotonin reuptake inhibitors (SSRIs). The COVID-19 pandemic, however, introduced unprecedented challenges through the implementation of non-pharmaceutical interventions (NPIs) that significantly restricted physical activity and increased mental health issues, specifically anxiety and depression. This longitudinal study used a community sample of Canadian young adults (n=443) to examine the association of the COVID-19 pandemic on commitment to exercise and associated effects on individual’s mental health outcomes across three time points over four years (from age 22 to 26). Contrary to prevailing literature, our findings did not reveal any consistent or strong associations between commitment to exercise and mental health symptoms within and across time. Although these results do not align with the established literature, they offer valuable insights and direction for future investigations in this domain. Given the insufficient availability of mental health professionals, it remains crucial for individuals and researchers to continue exploring the potential of physical activity and alternative interventions for mitigating mental health symptoms among young adults. Such efforts may contribute to the development of more accessible and cost-effective strategies for promoting psychological well-being among young adults and the general population.
Keywords: Mental Health; Anxiety; Depression; COVID-19; Commitment to Exercise; Physical Activity; Young Adults; Pandemic